2015
DOI: 10.1159/000440794
|View full text |Cite
|
Sign up to set email alerts
|

Microcalcification-Associated Breast Cancer: Presentation, Successful First Excision, Long-Term Recurrence and Survival Rate

Abstract: Introduction: In this study we evaluated mammographic, histological and immunohistochemical findings for microcalcification-associated breast cancer with regards to breast-conserving therapy, recurrence and survival rate. Patients and Methods: We retrospectively analyzed 99 consecutive, non-palpable and microcalcification-associated breast cancers (94 women) that were treated surgically between January 2002 and December 2003 at a national academic breast cancer center. Calcifications were classified according … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 38 publications
2
7
0
Order By: Relevance
“…However, little is known about the incidence of microcalcification-associated breast cancers [15]. Our study found that Luminal B tumors (Luminal B vs. others, Luminal B vs. Luminal A, Luminal B vs. basal) have the highest risk of LN metastasis.…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…However, little is known about the incidence of microcalcification-associated breast cancers [15]. Our study found that Luminal B tumors (Luminal B vs. others, Luminal B vs. Luminal A, Luminal B vs. basal) have the highest risk of LN metastasis.…”
Section: Discussionmentioning
confidence: 57%
“…A previous study reported that HER2 positivity is associated with a higher rate of LN metastases [ 23 ]; this was not confirmed by our study. However, little is known about the incidence of microcalcification-associated breast cancers [ 15 ]. Our study found that Luminal B tumors (Luminal B vs. others, Luminal B vs. Luminal A, Luminal B vs. basal) have the highest risk of LN metastasis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Before cancer cells find their way into the circulation, they may have to adopt an invasive phenotype, a phenomenon referred to as the epithelial-mesenchymal transition (EMT). During this adoption, an overlooked feature of breast tumors is the biological significance of microcalcifications in situ, mainly comprising of calcium oxalate or hydroxyapatite (76,77). This had been partly explored long back, where the osteotropism of breast cancer was correlated with its ability of inducing microcalcifications by expressing bone matrix proteins (78).…”
Section: Bone Metastasismentioning
confidence: 99%
“…This study finds the different characteristics of micro calcification and mass [20][21][22]. The information of centroid and radius provided in Mammographic Image Analysis Society (MIAS) database [23] are used to find and extract the micro calcification and mass.…”
Section: Introductionmentioning
confidence: 99%